Adenosine cyclic phosphate with ultrasonic-assisted pectinase extraction alleviated allergic reactions in RBL-2H3 through inhibiting the influx of intracellular Ca2+ - Qiao Bai; Xiaoping Feng; Yu Wang; Chunyu Wu; Ye Liu; Jiao Sun; Tianli Yue; Fangyu Long (Food Science and Human Wellness)
Jujube contains abundant cyclic adenosine monophosphate (cAMP) and the ultrasonic-assisted pectinase extraction (UAPE) conditions for obtaining the maximum cAMP yield from jujube were optimized. Orthogonal array design was applied to evaluate the effects of 4 variables by UAPE on cAMP yield. The results showed that the optimal cAMP yield (783.0 μg/g) was derived at ratio of liquid to solid 5 mL/g, ratio of pectinase to raw material 1.5 %, time 60 min and temperature 40 °C. Moreover, the effect of cAMP on the anti-allergic function of action induced by immunoglobulin E (IgE) and its meschanism was investigated through establishing the sensitized cell model in rat basophilic leukemia (RBL-2H3) cells using dinitrophenylated (DNP)-bovine serum albumin (BSA)-IgE. The results showed that cAMP interfered with sensitized cells, effectively inhibited the occurrence of basophil degranulation in dose dependence, and significantly reduced the activity of β-hexosamindase (β-hex), at the optimal concentration of 50 μg/mL. The level of anti-inflammatory factor interleukin-10 (IL-10) was promoted and the content of pro-inflammatory factor tumor necrosis factor-α (TNF-α) was suppressed by cAMP. In addition, influx of intracellular Ca2+ was repressed effectively. Our results demonstrate that jujube cAMP regulated the cytokine balance in the allergy pathway through blocking the influx of extracellular Ca2+, with the prevention of allergy symptoms.